Characterization of multidrug-resistant Acinetobacter ssp. strains isolated from medical intensive care units in Cali - Colombia. (Colombia Medica, 2017)
Introduction:The extensive use of antibiotics has led to the emergence of multi-resistant strains in some species of the genus Acinetobacter.Objective:To investigate the molecular characteristics of multidrug-resistant of Acinetobacter ssp. strains isolated from 52 patients collected between March 2009 and July 2010 in medical intensive care units in Cali - Colombia.Methods:The susceptibility to various classes of antibiotics was determined by disc diffusion method, and the determination of the genomic species was carried out using amplified ribosomal DNA restriction analysis (ARDRA) and by sequencing of the 16s rDNA gene. Also, the genes of beta-lactamases as well as, integrases IntI1 and IntI2 were analyzed by PCR method.Results:The phenotypic identification showed that the isolates belong mainly to A. calcoaceticus- A. baumannii complex. All of them were multi-resistant to almost the whole antibiotics except to tigecycline and sulperazon, and they were grouped into five (I to V) different antibiotypes, being the antibiotype I the most common (50.0%). The percent of beta-lactamases detected was: blaTEM (17.3%), blaCTX-M (9.6%), blaVIM (21.2%), blaIMP (7.7%), blaOXA-58 (21.2%), and blaOXA-51 (21.2%). The phylogenetic tree analysis showed that the isolates were clustering to A. baumannii (74.1%), A. nosocomialis (11.1%) and A. calcoaceticus (7.4 %). Besides, the integron class 1 and class 2 were detected in 23.1% and 17.3% respectively.Conclusion:The isolates were identified to species A. baumanii mainly, and they were multiresistant. The resistance to beta-lactams may be by for presence of beta-lactamases in the majority of the isolates.